SYNGAS DERIVED FROM CATALYTIC GASIFICATION OF FINE COAL WASTE USING INDONESIAN POTENTIAL CATALYST - Faizal, Muhammad; Aprianti, Nabila; Said, Muhammad; Nasir, Subriyer (Journal of Applied Engineering Science, 2021)
Fine coal waste from the coal mining process has not been used as clean energy even though the amount is very abundant in the world. The conversion of fine coal to syngas is a new way to increase the value of fine coal. Syngas composition, gas ratio, gasification efficiency, and heating value of syngas have been determined under various conditions of temperature (550-750 °C) and bentonite catalyst ratio (0-0.25). The results indicate that fine coal is the suitable raw material for the gasification process. At the highest temperature (750 °C), the gas composition consists of 42.6 vol% H2, 19.1vol% CO, 19.5 vol% CH4, and 7.9vol% CO2. The best performance was achieved when the catalyst/feed ratio is 0.25 with the gas composition of 54.3vol% H2, 26.2vol% CO, 23.8 vol% CH4, and 3.5vol% CO2, heating value and gasification efficiency were 19.72 MJ/Nm3 and 72.27% at 750 °C.